RANCANG BANGUN E-GOVERNMENT SEBAGAI UPAYA MEMBANTU MEWUJUDKAN PELAYANAN PEMERINTAH DESA TENGKURAK KABUPATEN SERANG ENGGUNAKAN FRAMEWORK LARAVEL - Afiani Maulidiyah (2021)
The era of the industrial revolution 4.0 has had an impact on all aspects of life, including aspects of governance, both the central government, regional governments and village governments. The Tengkurak Village Government currently has not utilized and optimized information technology as a tool in carrying out its government duties, including serving the village community and other stakeholders. The purpose of this research is to design and build an e-government information system with the Laravel framework that is useful for the Tengkurak village government in providing services to the community and other stakeholders, besides that the community can also find out about various information provided by the Tengkurak village government. The results of this study are in the form of an e-government information system that can provide various online information and services to village communities and other stakeholders.